R&D expenditure in G7 countries and implications for endogenous fluctuations and growth - Klaus Wälde; Ulrich Woitek (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2003)
The literature on endogenous growth cycles predicts countercyclical R&D expenditure. Aggregate R&D expenditure in G7 countries from 1973 to 1997 seems to be procyclical. Implications for future theoretical research are discussed.
Keywords: C2; E32; O41; 330; Cyclical Properties of R&D Expenditure; Growth Cycles; Forschungskosten; Wachstumszyklus; Neue Wachstumstheorie; Schätzung; G-7-Staaten